Hemodynamics of a stenosed carotid bifurcation - Luísa C. Sousa (2013)
A methodology for computational 3D reconstruction and structured hexahedral meshing for patient-specific hemodynamics analysis of the carotid artery bifurcation with a stenosis is presented. The purpose of this work is the use of anatomically realistic blood flow simulations by the finite element method (FEM) derived from in vivo medical imaging to make patient specific studies of flow phenomena associated with the development of atherosclerosis disease. Blood flow is described by the incompressible Navier-Stokes equations and the simulation is carried out under pulsatile conditions. The study of a diseased carotid bifurcation illustrates the extremely complex hemodynamical behaviour along the cardiac cycle.